Analysis and simulation of turbulent flow around an immersed body with constant temperature using the Immersed Boundary Method - Rômulo Damasclin Chaves dos Santos; Jorge Henrique de Oliveira Sales (The Journal of Engineering and Exact Sciences)
In this study, we present an immersed boundary method to analyze interactions between fluids and bodies in two-dimensional (2D) flows around complex geometries, focusing on heat transfer and turbulence. The method uses an Eulerian grid for the fluid, and another Lagrangian grid for the immersed body, ensuring conditions of no slip and considering heat exchanges. We use Navier-Stokes and energy equations with Smagorinsky (LES) and Spalart-Allmaras (URANS) turbulence models. A computational code was implemented to calculate lift, drag and Nusselt coefficients, comparing the results with previous studies at different Reynolds numbers. This research advances the understanding of fluid-body interactions in complex geometries and thermofluid dynamics.